ARTIFICIAL INTELLIGENCE AND ECONOMIC DEVELOPMENT: MAPPING OPPORTUNITIES FOR DEVELOPING COUNTRIES - Adi Susanto; Ahmad Junaidi; Dwi Koerniawati; Iyad Abdallah Al- Shreifeen (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
Artificial Intelligence (AI) is considered a future driver for accelerating economic development in developing countries. This study aims to assess the impacts and challenges of AI integration in critical sectors and its implications for economic growth and social inclusion in developing countries. The research method used in this study is the literature review method. The results show that AI has been successfully applied in the agriculture, health, education, and finance sectors in developing countries, contributing significantly to improving efficiency, service quality, and access. However, the implementation is faced with a number of challenges such as a lack of digital infrastructure, a shortage of labor skilled in information technology and AI, and data and privacy regulatory challenges. Further research also shows that cooperation between the government, private sector, and international bodies is crucial in overcoming these obstacles.